Polymorphism analysis of GDF9 and BMP15 genes and their association with litter size in crossbreed goats in Malaysia - Armiyas Shibesh Faris; Kenneth Francis Rodrigues; Basit Zeshan; Subir Sarker; Su Chui Len Candyrine; Mohammad Mijanur Rahman; Mohamad Asrol Kalam; Md Safiul Alam Bhuiyan (Research Square, 2025)
The goat industry plays a crucial role in Malaysia's economy, with breeds such as Katjang and Boer being the integral to mutton supply. However, achieving self-sufficiency in goat meat production is still challenging due to the insufficient local carcass supply. To address this issue, a crossbreeding program has been initiated to improve reproductive performance in local breeds. In mammals, there are BMP15 and GDF9 genes which are the components of TGF-β superfamily that are key regulators of ovulation and litter size. This study aimed to improve reproductive performance in crossbred goats from Katjang and Boer populations in Sabah, Malaysia, by analyzing genetic variations in the BMP15 and GDF9 genes. A total of sixty female cross-Katjang goats, with recorded litter size and parities were sampled. Five milliliters of blood were taken from the jugular vein using K2-EDTA tubes. Genetic analysis was performed using conventional PCR at Biotechnology Research Institute, University Malaysia Sabah, followed by sequencing at Apical Scientific, Malaysia. Four novel polymorphic loci were identified within the GDF9 gene: G320C, A352G, G366T, and G375T. All of these loci resulted in missense mutations, causing a change in amino acid sequences. Notably, the A352G and G375T loci showed significant associations with litter size, with the AG genotype at position 352 and the GG genotype at position 375 emerging as potential markers for selective breeding. However, the polymorphic information content (PIC)values indicated low genetic diversity (< 0.25) at these loci. Interestingly, no polymorphisms were detected in the BMP15 gene, suggesting a monomorphic state (wild-type genotype) in the Cross-Katjang goat population. This finding indicates that BMP15 may not play a significant role in litter size variation in this crossbreed, shifting the focus towards GDF9 as a more relevant genetic marker for enhancing reproductive traits. This study provides important insights into the genetic factors influencing reproductive traits in crossbred goats, with potential applications in marker-assisted selection to improve reproductive and productivity performance.